INTERSECTIONS OF KNOWLEDGE, POWER AND RESISTANCE IN THE POETRY OF MAYA ANGELOU - KABERIA, TERESIA WANJIRU (Machakos University Press, 2022)
Guided by hermeneutics, intersectionality and Mikhail Bakhtin’s concept of dialogism, the study investigated manifestations of knowledge, power and resistance as motifs in Maya Angelou’s poetry. Hermeneutics was used in the analysis and interpretation of manifestations of knowledge, power and resistance in various contexts, Bakhtin’s concept of dialogism was used to explore how language is used to foreground power relations society, and Intersectionality enabled the analysis of how various socio-historical factors coalesce to bring out Maya’s worldview for a just society. The study adopted a descriptive research design with primary data obtained from twenty-nine purposively selected poems from The Complete Collected Poetry of Maya Angelou. Thematic content analysis was used in the analysis and interpretation of the poems. Findings from the study revealed that various contexts, such as historical and socio-cultural, and language converge to foreground knowledge, power and resistance in Angelou’s poetry. Additionally, the findings showed that intersections of knowledge, power and resistance contribute to the understanding of Angelou’s worldview for a just society.